Design and Implementation of a Web-Based Reservation Information System and Historical Portal at D'bubuy Ma'atik - Faresya Muryanti; Qisty Sauva; Ryan Piarna (Expert Net: Exploration Journal of Technological Education Trends, 2025)
D’bubuy Ma’atik is a widely recognized traditional culinary establishment, yet it faces operational challenges due to a manual reservation system conducted through instant messaging applications. The lack of official documentation regarding the history of bubuy dishes has led to inconsistent cultural information and customer service inefficiencies. This research aims to design and develop a web-based information system that integrates online reservation features with a historical portal as an effort toward traditional culinary digitalization. The research method employed is the Waterfall model, which includes stages of requirements analysis, system design using Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD), implementation using Native PHP and MySQL, and functional testing via Black Box Testing. The results indicate that the developed system successfully automates price calculations and data recording, thereby reducing administrative time and closing loopholes for payment proof manipulation through centralized admin validation. Furthermore, the historical portal feature provides a permanent digital repository that preserves the philosophical values of the cuisine, ensuring they remain easily accessible to customers. The system implementation not only enhances operational efficiency and transaction security against fictitious orders but also strengthens the preservation of local culinary heritage through structured digital information accessibility.